ANALYSIS OF STUDENTS' INTEREST IN LEARNING AND MOTIVATION LEARNING PHYSICS: A CASE STUDY AT SMAN 9 BANDA ACEH YEAR 2023/2024 - Miswatul Hasanah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The case study aims to determine students' interest and motivation during thelearning process in physics subjects with material on rectilinear motion andstatic fluids. The population of this study were students in classes X and XI atSMAN 9 Banda Aceh for the 2023/2024 academic year. The selected researchsamples were students in classes X MIPA 2 and XI MIPA 4, totaling 20 and 29students respectively. This research uses descriptive research with a qualitativeapproach. Data collection was carried out through observing student activities,observing student responses, interviews, and documentation. Based on theresults of the case study that has been carried out, it is concluded that studentactivity in learning physics can be categorized as low with the percentage dataobtained for class X MIPA 2 being 42.78% and the percentage for class XIMIPA 4 being 50.56%. The physics learning process still uses conventionalmethods and the media used in the learning process is a whiteboard. The resultsof interviews with teachers stated that students were not enthusiastic and lazyin learning physics. This indicates that students have low interest andmotivation towards learning.